Empowering Equality: Mubadalah as a Catalyst for Peace, Justice, and Harmony Among Humanity - Dini Amalia (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2024)
This article explores the transformative concept of Mubadalah, seeking to unravel its potential as a powerful catalyst for fostering justice and harmony among humanity. Mubadalah often overlooked in discussions surrounding equality, emerges as a promising framework that goes beyond conventional approaches. By examining its principles and applications, using documentative and library research, this exploration aims to shed light on how Mubadalah can be harnessed to address societal imbalances and promote inclusivity. Drawing on real-world examples and theoretical perspectives, the article navigates the intricate landscape of Mubadalah, highlighting its capacity to cultivate a more equitable and just global community. Through a comprehensive qualitative analysis, the valuable insights into the potential of Mubadalah are expected to contribute significantly to the pursuit of a more harmonious and egalitarian peaceful world.